IgA vasculitis induced by carboplatin + nab-paclitaxel + pembrolizumab in a patient with advanced lung squamous cell carcinoma: a case report - Terashima, Yuto; Matsumoto, Masaru; Ozaki, Saeko; Nakagawa, Michiko; Nakagome, Shun; Terasaki, Yasuhiro; Iida, Hiroki; Mitsugi, Ryotaro; Kuramochi, Eri; Okada, Naoko; Inoue, Tomoyasu; Matsuki, Satoru; et al. (Frontiers in Immunology, 2024)
A 73-year-old man with lung squamous cell carcinoma was administered carboplatin + nab-paclitaxel + pembrolizumab for four cycles. Subsequently, he presented with multiple purpuras on his extremities, joint swelling on his fingers, abdominal pain, and diarrhea, accompanied by acute kidney injury (AKI), increased proteinuria, hematuria, and elevated C-reactive protein levels. Skin biopsy showed leukocytoclastic vasculitis as well as IgA and C3 deposition in the vessel walls. Based on these findings, the patient was diagnosed with IgA vasculitis as an immune-related adverse event (irAE) induced by carboplatin + nab-paclitaxel + pembrolizumab. After discontinuation of pembrolizumab and glucocorticoids, the symptoms immediately resolved. Regular monitoring of skin, blood tests, and urinalysis are necessary, and the possibility of irAE IgA vasculitis should be considered in cases of purpura and AKI during treatment with immune checkpoint inhibitors.